Integrated light chemical tagging analyses of seven M31 outer halo globular clusters from the Pan-Andromeda Archaeological Survey - Sakari, Charli M.; Venn, Kim A.; Mackey, Dougal; Shetrone, Matthew D.; Dotter, Aaron; Ferguson, Annette M. N.; Huxor, Avon P. (Monthly notices of the Royal Astronomical Society, 2015)
ABSTRACT. Detailed chemical abundances are presented for seven M31 outer halo globular clusters (with projected distances from M31 greater than 30 kpc), as der
Gesehen am 09.07.2020